Peluang dan Tantangan Pengembangan Budidaya Ulat Sutera dalam Persprektif Geografi - Rosmini Maru; Nasiah Badwi; Ibrahim Abbas; Sudirman Sudirman; Nurfadilah Nurfadilah; Medar M Nur; Nur Fatima Basram (LaGeografia, 2021)
This research is basic research that aims to reveal the event of silkworm cultivation in Enrekang Regency, also as how the opportunities and challenges faced within the future. Furthermore, the long-term goal of this research is to take care of and increase silk production to satisfy local, national, and export needs, with the hope of accelerating people's income, local native income (PAD), and foreign exchange. The method used may be a survey to watch and measure various influential variables. Data utilized in the shape of secondary and first data. The data analysis used is a cartographic analysis. supporting factors for the event of silkworm cultivation in Enrekang subdistrict are; the simplest quality, abundant sources of feed, abundant human resources, sheltered by state-owned enterprises, near the axis roads, tools and cultivation materials are available and easy to obtain, cooperation with other regions, cheap seeds, high purchasing power, and government visits and tourists. supporting factors there also are factors inhibiting the event of silkworm cultivation in Enrekang Regency, namely: it's begun to be left behind, caterpillars are too sensitive, simple cultivation techniques, alittle amount of harvest, cultivation of households (nongroup), the transfer of murberi land functions, uncertain climate, the breakup of subsequent generation, promising work and yarn / imported fabrics.